PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN MEDIA PEMBELAJARAN TRACKER TERHADAP HASIL BELAJAR PESERTA DIDIK SMA KELAS XI PADA MATERI GERAK PARABOLA - Mawu, Mulia; Mondolang, Aswin Hermanus; Lolowang, Jimmy; Tumangkeng, Jeane Verra; Silangen, Patricia Mardiana (Charm Sains: Jurnal Pendidikan Fisika, 2025)
Guided inquiry encourages students actively identify problems, create hypotheses, conduct experiments, analyze data, and draw conclusions. Tracker helps students understand physics concepts by analyzing objects in parabolic motion, and visualizing relation between variables through graphs and tables. This study aimed to examine effect of guided inquiry model with Tracker on high school students’ learning outcomes in parabolic motion. The method used Quasi-Experiment with pretest-posttest control group design. The population is 11th-grade students at SMA Negeri 1 Kawangkoan Barat with samples experimental class XI A and control class XI B.The test instruments included multiple-choice and essay questions. After treatment, the experimental class's average score showed significant increase 54 to 81, higher than control class 50.75 to 66.25. Hypothesis testing (SPSS) led to rejected H0 and H1 accepted. Its concluded that guided inquiry with Tracker positively affects learning outcomes by boosting student engagement and comprehension.